Treatment inferred from mutations identified using massive parallel sequencing leads to clinical benefit in some heavily pretreated cancer patients. Issue 20 (May 2017) - Zick, Aviad; Peretz, Tamar; Lotem, Michal; Hubert, Ayala; Katz, Daniela; Temper, Mark; Rottenberg, Yakir; Uziely, Beatrice; Nechushtan, Hovav; Meirovitz, Amichai; Sonnenblick, Amir; Sapir, Eli; et al.
Abstract : Abstract: Molecular portraits of numerous tumors have flooded oncologists with vast amounts of data. In parallel, effective inhibitors of central pathways have shown great clinical benefit. Together, this promises potential clinical benefits to otherwise end-stage cancer patients. Here, we report a clinical service offering mutation detection of archived samples using the ion Ampliseq cancer panel coupled with clinical consultation. A multidisciplinary think tank consisting of oncologists, molecular-biologists, genetic counselors, and pathologists discussed 67 heavily pretreated, advanced cancer patient cases, taking into account mutations identified using ion Ampliseq cancer panel, medical history, and relevant literature. The team generated a treatment plan, targeting specific mutations, for 41 out of 64 cases. Three patients died before results were available. For 32 patients, the treating oncologists chose not to include the panel recommendation in the treatment plan for various reasons. Nine patients were treated as recommended by the panel, 5 with clinical benefit, and 4 with disease progression. This study suggests that routine use of massive parallel tumor sequencing is feasible and can judiciously affect treatment decisions when coupled with multidisciplinary team-based decision making. Administration of personalized based therapies at an earlier stage of disease, expansion of genetic alterations examined, and increased availability of targeted therapies may lead to further improvement in the clinical outcome of metastatic cancer patients.